Parerga to the Stadiasmus Patarensis (2): Sidyma I. The History of the Settlement with the New Inscriptions - Burak Takmer (Gephyra, 2010)
The contribution introduces six inscriptions, from a total of fourteen new inscriptions, providing information concerning the history of the city, its territory, prominent citizens who obtained Roman citizenship and the funerary architecture that is peculiar to this city. Before the author introduces these inscriptions, he provides the following four items: (I) urban topography and the monuments on surface, (II) the history of the settlement, (III) the Roman citizens before the Constitutio Antoniniana and (IV) the territory of the city. Accordingly, there is the Hellenistic-Classical fortification wall, the theatre, agora, a Doric-style stoa, which Ti. Claudius Epagathos, the freedman and personal physician of the Emperor Claudius, and his son Ti. Claudius Livianus dedicated to the emperor, a sebasteion dedicated to θεοὶ σωτῆρες Σεβαστοί during the governorship of Quintus Veranius, the first governor of the province. In Sidyma, furthermore there are about one hundred funerary constructions of diverse typologies, built in different periods from 5th century BC to the 5th century AD. The earliest remains of the city date from the Classical Period. Further evidence indicating the existence of the city in the Classical Period comes from the tribute lists of 425/4 BC of the Athenian-Delian League, mentioning the name of Sidyma. The Classical fortification walls must have been strengthened by the 3rdcentury BC, during the Galatian invasions. Sidyma was one of the eighteen cities with the right to mint coins in the 2nd century BC. The city, at the same time, in addition to the rich funerary architecture and the rise of its citizens to obtaining the highest posts in the Lycian League from the establishment of the province, experienced its most prosperous age between the 1st and 3rd centuries AD, as the existence of citizens with a consular career indicates. Sidyma may have played a role in the civil strife which prepared the ground for the annexation of Lycia in AD 43, and in consequence experienced this prosperity. The remains of 5 churches-chapels and the fort on the uppermost part of the acropolis indicate the settlement continued into the Byzantine Period. After this, the author introduces the first inscription which concerns the history of the city and which bears the title Divus Augustus. This inscription shows Sidyma participated with the other Lycian cities in expressing its loyalty to Augustus and to associate the city with the new world order. The second inscription in which Plotina Augusta was honoured must have been raised in 117 when Traianus was understood to visit Lycia with his wife on their return from the Parthian campaign. The third is a funerary inscription that records Hoplon from Kalaba(t)tia, a harbour settlement connected by road in the reign of Claudius to Sidyma, built this tomb-monument for himself and for his family. The fourth inscription carries evidence of the educational establishments of the city (paidonomia and gymnasiarkhia), while the fifth inscription mentions an association (collegium) founded by the middle class (plebs media) to strengthen their social status against the upper class (honestiores) of the city. The sixth inscription records the presence of a graveyard which contained the family burials of the Claudii and the Caristanii. In addition, this inscription importantly documents a unique example of a temple-tomb from Sidyma which contained a sarcophagus in the cella.